THE DANCE AND ITS INFLUENCE OVER THE CHILD'S SOCIAL ABILITIES AT SCHOOL AGE (Fiep Bulletin - online, 2011)
This study, of a qualitative nature, has the purpose of deepening the knowledge about the relationship between dance, an art, and its possible influences over the development of social skills of children in school age. The study was composed of two steps, first for literary revision and the second concerning an exploratory research, developed through a survey applied to parents of students who participated in the study, 16 girls from 7 to 11 years, who had frequency exceeding 70% in Universidade Positivo project "Initiation to Sports – Dances – 2009". From the analysis of literary revision and parents awareness about their daughters, we found that the dance at school age is a powerful instrument to develop or enhance social skills, thereby, lowering the chances of those children present behaviors of risk in adolescence and therefore causing irreparable harm throughout their lives..
Keywords: Dance; Social Development; School Age